Alexithymia in multiple sclerosis: past, present and future - Samar S. Ayache; Samar S. Ayache; Samar S. Ayache; Samar S. Ayache; Moussa A. Chalah; Moussa A. Chalah; Moussa A. Chalah (Frontiers in Human Neuroscience)
Alexithymia denotes the “absence” of “words” for “emotion” and has its roots in the Greek words “a,” “lexis,” and “thymos.” It is sometimes referred to as “emotional blindness,” “blunted feeling,” or “disrupted emotional awareness.” The term “alexithymia” first appeared in the 1970s in the works of Sifneos, Nemiah, and colleagues. It entails difficulties in identifying and expressing emotions and an externally oriented thinking style. It is not a psychiatric disorder but rather a multidimensional personality trait or construct, appearing to be normally distributed in the general population, with high levels of alexithymia in approximately 10% of individuals. Evidence suggests that alexithymia serves as a prognostic risk factor for health problems, a transdiagnostic risk factor for emotion-based psychopathologies, and a predictor of poor psychiatric treatment outcomes. It is frequently observed in neurological diseases. Nevertheless, its mechanisms, assessment, and management remain overlooked. In multiple sclerosis (MS), an autoimmune disease of the central nervous system, alexithymia seems to occur in up to 53% of patients. However, it remains understudied despite recent growing interest. In this mini review, we briefly reassess the prevalence, as well as the clinical, sociodemographic and neuropsychological correlates of alexithymia in MS (e.g., anxiety, depression, fatigue, socio-emotional outcomes). This is followed by an analysis of neurobiological underpinnings of alexithymia derived from neurophysiological and neuroimaging studies in this clinical population. Finally, we provide perspectives to guide future research exploring and managing alexithymia in MS.